4x+21x-1=5(5x+9)

Simple and best practice solution for 4x+21x-1=5(5x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+21x-1=5(5x+9) equation:



4x+21x-1=5(5x+9)
We move all terms to the left:
4x+21x-1-(5(5x+9))=0
We add all the numbers together, and all the variables
25x-(5(5x+9))-1=0
We calculate terms in parentheses: -(5(5x+9)), so:
5(5x+9)
We multiply parentheses
25x+45
Back to the equation:
-(25x+45)
We get rid of parentheses
25x-25x-45-1=0
We add all the numbers together, and all the variables
-46!=0
There is no solution for this equation

See similar equations:

| 3x+40=58 | | -3=-3x³-2 | | 3n-2+2(2n+1=n+5n+7= | | -1(-1+7x)-6(-7-x)=36 | | 3x-5(x-4)=-9=5x=8 | | 2/3x^2+6=18 | | 3m/4-12=2m-7 | | 3(n-1)=3n-9 | | 2=1x+6 | | 74-13x=355 | | 16+6y=84 | | 2(4R+7)=8r+14 | | 6-3g=5g-10g+12 | | 32x=28*8 | | 6x+20=590 | | 3b+5=4(2b-5) | | 24x-1=6(4x-2) | | 2(5+b)+b=34 | | 27m=135*9 | | 9v-5v+32=-8 | | -31+8x=8(x-5)+3 | | -12+17p=-8+18p+12 | | (76-2x)=(90-3x) | | -5+x-(2-x)=-3 | | 1=-5/4y | | 10/7=r−(−5/8) | | x=4x-61 | | 23/8=46/p | | -72=12r | | -20n-11n-20=-16 | | -16.4f-18.74=19.2+18.06-5.2f | | 16÷7=-8x |

Equations solver categories